Bali traditions and tourism - Pro Doco (Firm) (Australia : Pro Doco, 2002)
Bali, Indonesia, is one of the world's most exotic and interesting islands. Here the traditional way of life, customs and beliefs continue side by side with changes brought by tourism.
Part 1. Bali: Traditions and tourism . - Part 2. Bali terrorist bombings Oct. 2002
DVD format
Keywords: Tourism -- Bali Island (Indonesia); Bali Island (Indonesia) -- Religious life and customs